Pengaruh Gaya Komunikasi, Fasilitas, dan Iklim Organisasi terhadap Kinerja Pegawai di DPMPTSP Pidie Jaya - Shahibul Azmi; Tarmizi Gadeng; Tuwisna Tuwisna (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of Leadership Communication Style, Work Facilities, and Organizational Communication Climate on employee performance at the Pidie Jaya Investment and One-Stop Integrated Service for Manpower and Transmigration. The research method used is an associative method with a quantitative approach, while data collection is carried out by distributing questionnaires to all employees using a census technique. A total of 40 employees became respondents in this study. The results of the analysis show that partially, Leadership Communication Style, Work Facilities, and Organizational Communication Climate each have a significant effect on employee performance. In addition, these three variables also have a simultaneous effect on employee performance. This finding confirms that the better the communication style applied by the leader, supported by adequate work facilities and a conducive organizational communication climate, the greater the potential for improving employee performance. Therefore, it is important for this agency to continue to improve these three factors so that employee productivity and work effectiveness can be increasingly optimal, supporting the achievement of organizational goals as a whole.